Fatigue, Work Schedules, and Perceived Performance in Bedside Care Nurses. (July 2017) - Sagherian, Knar; Clinton, Michael E.; Abu-Saad Huijer, Huda; Geiger-Brown, Jeanne
Hospital nurses are expected to maintain optimal work performance; yet, fatigue can threaten safe practice and result in unfavorable patient outcomes. This descriptive cross-sectional study explored the association between fatigue, work schedules, and perceived work performance among nurses. The study sample included 77 bedside nurses who were mostly female, single, and between 20 and 29 years of age. The majority worked 8-hour shifts and overtime. Nurses who worked during off days reported significantly higher chronic fatigue compared with those nurses who took time off. Nurses who reported feeling refreshed after sleep had significantly less chronic and acute fatigue and more intershift recovery. Nurses with acute and chronic fatigue perceived poorer physical performance. Also, nurses who reported chronic fatigue perceived they were less alert and less able to concentrate when providing patient care. Less effective communication was also associated with acute and chronic fatigue. In conclusion, fatigue has safety implications for nurses' practice that should be monitored by nursing management.